Microstructural Characterization of Natural Fibers: Etlingera elatior, Costus comosus, and Heliconia bihai. (24th October 2013) - Navarro, Cláudia I. T.; Paciornik, Sidnei; d'Almeida, José R. M.
Abstract : This work describes the structural and morphological characteristics of fibers obtained from the stem of three ornamental plants, namely, Etlingera elatior, Costus comosus, and Heliconia bihai . The stems of these plants are long and nowadays do not have any use, being disregarded. The results obtained showed that the three fibers have a crystalline index of around 58% and are thermally stable to approximately 230°C, 240°C, and 255°C for E. elatior, C. comosus, and H. bihai, respectively. The fibers present an average humidity amount of less than 9% and the thermal degradation peak for the cellulose component varies from 358°C for E. elatior to 379°C for C. comosus . The morphological analysis showed that the fibers present a large variability of the shape of their cross-sections, which are preferentially elongated. These morphological characteristics were used to estimate the error made when one considers the fibers having a circular cross-section.